An Energy Conserving Modification of Numerical Methods for the Integration of Equations of Motion - LaBudde, Robert; Greenspan, Donald (University of Wisconsin-Madison Department of Computer Sciences, 1974)
In the integration of the equations of motion of a system of particles, conventional numerical methods generate an error in the total energy of the same order as the truncation error. A simple modification of these methods is described, which results in exact conservation of the energy.